Green Synthesis of Silver Nanoparticles from Moringa Oleifera Leaf Extract and Its Antibacterial Activity (Minang Chemistry Journal (MCJ), 2026)
This study reports the rapid green synthesis of silver nanoparticles (AgNPs) using Moringa oleifera leaf extract as a reducing and stabilizing agent. The synthesized nanoparticles were characterized using UV-Vis spectroscopy, XRD, and TEM. The UV-Vis spectrum showed a characteristic surface plasmon resonance peak at 420 nm. The AgNPs exhibited significant antibacterial activity against E. coli and S. aureus, making them promising candidates for bio-medical applications.